The role of personality, authoritarianism and cognition in the United Kingdom’s 2016 referendum on European Union membership - Sumner, Chris; Scofield, John E.; Buchanan, Erin M.; Evans, Mimi-Rose; Shearing, Matthew (Frontiers in Psychology, 2023)
Introduction The results of the United Kingdom’s 2016 referendum on European Union (EU) membership have highlighted deep societal divides. In six studies, we examined the role of personality traits, cognition and cognitive biases in relation to referendum voters’ choices. Methods A total of 11,225 participants completed questionnaires and controlled experiments, which assessed differences in personality traits, levels of authoritarianism, numeracy, thinking styles, and susceptibility to cognitive biases including ideologically motivated numeracy and reasoning, framing, and the Dunning-Kruger effect. Results Participants expressing an intent to vote to leave the EU reported significantly higher levels of authoritarianism and conscientiousness, and lower levels of openness and neuroticism than voters expressing an intent to vote to remain in the EU. When compared with Remain voters, Leave voters displayed significantly lower levels of numeracy and appeared more reliant on impulsive System 1 thinking. In the experimental studies, voters on both sides were found to be susceptible to the cognitive biases tested, with a general trend for Leave voters to show more bias than Remain voters. Discussion These results raise important questions regarding the use and framing of numerical and non-numerical data for public consumption.